PELATIHAN TENTANG KURIKULUM 2013 PADA GURU-GURU SD GMIM DI KECAMATAN TONDANO KABUPATEN MINAHASA - Devyano Ranti (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2016)
Curriculum was essential for the formal education. Any shift or renewing in curriculum strucure aim for the better learning outcomes. The implementation of new 2013 curriculum was not thoroughly applied in all scholls. Governement implement thi curriculum gradually. It create discungruance in schools standards. This research aim to narrow the gap of schools that by government had impelement 2013 curriculum and other schools who had not. The programmes was conducted in lecturing, discussing and exercising to master the 2013 curriculum. This programme was conduct at SD GMIM Koya and the target was teachers. As result Teacher has the understanding and ability in fulfilling the curriculum requirement. They now have implemented the curriculum and have the same standard with others that have implemented it earlier.